Mythos vs Myth (Minerva, 2019)
In current research on Greek religion and literature in the wake of M. Detienne and C. Calame there is a wide-spread belief that the Greeks never elaborated a single concept or definition of mythos as a coherent notion corresponding to that of myth, and that the modern category of myth is a recent Eurocentric construction and not a universal mode of human thought. Basing on philological investigation of some overlooked Greek and Latin evidence (esp. Aristoteles and Varro) and results of cognitive and anthropological studies applied to religion we make a plea for the opposite view. Our conclusion is that myth is a pan-human occurrence to be considered a subspecies of symbolic phenomena and that the large body of tales that the Greeks called mythoi was indeed recognized as a distinct category of stories.
Keywords: myth; symbol; religión; history